Implementation of Halal Industry Financing Schemes in Indonesia: Strategies and Challenges - Supardi, Sania Faradila Aisyah; Nurwahidin, Nurwahidin (Journal Of Middle East and Islamic Studies, 2026)
The link between the Halal Industrial Ecosystem and Sharia Finance has become an increasingly relevant and significant topic in the context of the rapidly developing global economy. This study aims to identify how the halal industry and Islamic finance support each other in an increasingly complex ecosystem. This study uses a literature review method that discusses the role of Islamic finance in providing financing support in accordance with Sharia principles for the halal industry, which includes financing for working capital, investment, and risk protection. Furthermore, this study also identifies the challenges faced by Islamic finance in supporting the halal industry, including issues such as long-term financing needs, immature Islamic financial infrastructure, and challenges in evaluating the feasibility of businesses that comply with halal principles. The results of this study highlight the importance of collaboration between halal industry stakeholders and Islamic financial institutions such as Islamic Banking, the Social Security and Non-Bank Financial Institutions (IKNB) sectors, the Islamic Capital Market sector, and the Zakat and Waqf sector in addressing these challenges and facilitating sustainable economic growth in the halal industry. It also provides important insights into the potential for closer cooperation in the future.